Profile of an occupation – optician - Schambeck, Arne [Verfasser] (My University, 2023)
"Optician is a training occupation for people who enjoy advising customers, appreciate highly precise work and would like to use technical skills. This description of an occupation explores the most important tasks and why the employment opportunities for trained opticians are so good." (author's abstract; BIBB-Doku)
Keywords: S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); 370; Augenoptiker; Berufsbild